Comparison of the effect structure on ring and linear cavity lasers of erdoped optical fibers - Sellami , Ali; Al-Khateeb, Khalid A. Saeed; Billoui, Bouzid (2008)
Two erbium doped fiber laser configurations are conceived and constructed; A ring fiber laser and a linear cavity fiber loop laser. A comparative investigation tests were carried out. It is found that both the output power and the side mode suppression ratio (SMSR) for the two structures were significantly different. The measured laser power and the side mode suppression ratio (SMSR) of 11 mW and 75 dB respectively were higher for the linear cavity configuration. A lower output power and SMSR of 3 mW and 61.5 dB respectively were obtained with the ring laser configuration. Both lasers were pumped with a 90 mW pump power, and had a reflectivity of 90%.